2021
DOI: 10.31294/jtk.v7i2.10474
|View full text |Cite
|
Sign up to set email alerts
|

Prediksi Status Pinjaman Bank dengan Deep Learning Neural Network

Abstract: Penilaian risiko pada penentuan status pinjaman merupakan proses yang penting dalam usaha simpan pinjam. Prediksi dalam mengklasifikasikan apakah nasabah akan melunasi atau tidak akan menentukan pengambilan keputusan dan tindaklanjutnya yang berdampak pada kinerja entitas dalam menjalankan usahanya. Berbagai teknik dalam prediksi status pinjaman dengan machine learning diterapkan dengan hasil yang meningkat dalam akurasi dan performance. Metode Deep Learning Neural Network (DNN) merupakan salah satu metode mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Each of these algorithms has advantages and disadvantages because they can create prediction models with their own characteristics/methods. From research [6] and more complex, which is not suitable for this cooperative dataset, which is quite small. This was also found in credit risk analysis research [7] who found that tree-based models were more stable than models based on multilayer artificial neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these algorithms has advantages and disadvantages because they can create prediction models with their own characteristics/methods. From research [6] and more complex, which is not suitable for this cooperative dataset, which is quite small. This was also found in credit risk analysis research [7] who found that tree-based models were more stable than models based on multilayer artificial neural networks.…”
Section: Introductionmentioning
confidence: 99%
“…Credit risk is among the top five risks that pose significant challenges to the banking industry or other financial institutions (Syafudin et al, 2021). Credit risk assessment is crucial in determining whether a customer can repay their debt or is at risk of default.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, creditors need to develop predictive models of default status to assess customers' repayment abilities, thus reaching out to individuals without a credit history. Manual credit risk assessment predictions are subjective and susceptible to fraud (Syafudin et al, 2021). method has also been used to predict delinquent loan payments at PT FIF Group Arjawinangun Branch, resulting in an accuracy of 71% (Pratama et al, 2021).…”
Section: Introductionmentioning
confidence: 99%